Diplomacia y política - Elsa Caula (Mélanges de la Casa de Velázquez)
The present article analyses the complexity of political and diplomatic relationships of Iberic monarchies between the Portuguese invasion to the oriental province, and the events which sealed the  swearing of the Cadiz constitution by Fernando VII, during the critical Rioplatense political environment, which continued on the return of the Casa de Braganza to Portugal. It studies the management developed by the representative of the Spanish legation to Rio de Janeiro, the count of casa Flórez, in order to create an espionage propaganda net, whose aim it was to wait for the arrival of the Reconquest Great Expedition in order to put an end to the independence of the Provincias Unidas of the South, identifying their participants and their interventions. It provides evidence on phenomena and situations that highlight the need to study the independence history of the Iberic monarchies without borders.